Prevalence of Generalized Anxiety Disorder and its effect on Daily Living in the Rural Community of Rajshahi - Haque, MJ; Das, CK; Ara, R; Alam, MEU; Ullah, SKRKMASSA; Hossain, ZMM (TAJ: Journal of Teachers Association, 2018)
This cross-sectional type of descriptive study was conducted in three villages of Puthia Upazila under Rajshahi district to find out the prevalence of Generalized Anxiety Disorder (GAD) and its effect on their daily living. A total of 876 adult people of aged 18 years and above, were selected purposively. Data were collected by face to face interview with the help of a semi-structured questionnaire which contained Hamilton’s 7-point anxiety scale. Out of 876 respondents, 80% had GAD, where mild, moderate and severe GAD being 42.5%, 31.8% and 5.7% respectively. GAD was found to be more frequently associated in the 3rd and 5th decades of life, which constituted 27% and 12.9% respectively (p < 0.001). Having GAD, females have more ability to cope with daily living than males, though GAD was not found to be associated with sex (p >0.05). Illiterate and primary level educated respondents were more often associated with GAD (40.4 and 25% respectively) than the SSC and higher level educated people (p < 0.001). Businessmen were found to be significantly associated with GAD (29.7%) than the other occupations (p < 0.001). Poor people tend to be associated with GAD significantly more than the middle class and the rich (p < 0.01). Widow(er) and married and living together were likely to have GAD than the single or divorced or separated (p < 0.001). Activities of daily living gradually becoming more difficult when intensity of anxiety status increased which is statistically significant (p<0.001).The association between sex and problem facing in everyday life shows that over 40% of the females did not have any difficulty in dealing with problem situation as compared to only 25.8% of the males, while nearly half (48.6%) of males had quite difficulty in dealing with a problem as compared to 37.3% in females (p < 0.001). The present study concluded that majority rural adult people (4 in every five) suffer from generalized anxiety disorder (GAD). The ability of coping with a problem is higher in females than the males. This study might be the basis for further in depth study in this regard. TAJ 2014; 27(1): 14-23